Influencers on deprescribing practice of primary healthcare providers in Nova Scotia: An examination using behavior change frameworks - Natalie Kennie-Kaulbach; Rachel Cormier; Olga Kits; Emily Reeve; Anne Marie Whelan; Ruth Martin-Misener; Fred Burge; Sarah Burgess; Jennifer E. Isenor (Medicine Access @ Point of Care, 2020)
Background: Deprescribing is a complex process requiring consideration of behavior change theory to improve implementation and uptake. Aim: The aim of this study was to describe the knowledge, attitudes, beliefs, and behaviors that influence deprescribing for primary healthcare providers (family physicians, nurse practitioners (NPs), and pharmacists) within Nova Scotia using the Theoretical Domains Framework version 2 (TDF(v2)) and the Behavior Change Wheel . Methods: Interviews and focus groups were completed with primary care providers (physicians, NPs, and pharmacists) in Nova Scotia, Canada. Coding was completed using the TDF(v2) to identify the key influencers. Subdomain themes were also identified for the main TDF(v2) domains and results were then linked to the Behavior Change Wheel—Capability, Opportunity, and Motivation components. Results: Participants identified key influencers for deprescribing including areas related to Opportunity , within TDF(v2) domain Social Influences , such as patients and other healthcare providers, as well as Physical barriers (TDF(v2) domain Environmental Context and Resources ), such as lack of time and reimbursement. Conclusion: Our results suggest that a systematic approach to deprescribing in primary care should be supported by opportunities for patient and healthcare provider collaborations, as well as practice and system level enhancements to support sustainability of deprescribing practices.